THE RISK FACTORS AND SPECIFIC FEATURES OF OSTEOPENIC SYNDROME IN PATIENTS WITH CHRONIC NON-INFECTIOUS DISEASES - N. G. Platitsyna; T. V. Bolotnova (Klinicist)
Objective: to analyze the risk factors (RFs) of osteoporosis (OP), the risk of OP-related fractures, the specific features of osteopenic syndrome in patients with chronic non-infectious diseases (CNID) (coronary heart disease (CHD), hypertension, chronic obstructive pulmonary disease (COPD), and asthma). Materials and methods. The investigation enrolled 377 patients (mean age 55.3 ± 1.6 years) with CNID and 221 persons (mean age, 53.2 ± 1.3 years) who formed a control group. According to the nosological entity, the patients were divided as follows: Group 1 included 84 patients with CHD and hypertension; Group 2 comprised 99 hypertensive patients; Group 3 consisted of 70 patients with COPD; and Group 4 included 124 asthmatic patients. The examinees of all the groups were matched for age, gender, and body mass index. The investigation excluded patients with functional class IV chronic heart failure, continuous atrial fibrillation, heart valve disease, or myocardial noncoronarogenic diseases and those with other diseases and conditions that could have an independent impact on bone metabolism. Prior to the examination, the patients had received no specific therapy for the prevention and treatment of OP. RFs for OP were assessed using the one-minute test recommended by the International OP Foundation (2008); 10-year risk for OP-related fractures were calculated applying the FRAX computer program in accordance with the guidelines of the International OP Association and the World Health Organization (WHO, 2008). To investigate bone mineral density (BMD), bioenergy X-ray densitometry of the lumbar spine and proximal femur was carried out by means of a Lunar DPX apparatus (USA). The results were assessed using the t-test in standard deviations (SD) from the peak bone mass according to the WHO guidelines. Results. The RFs of OP were more frequently recorded in the patients with CNID than in the healthy individuals. RFs, such as smoking, low physical activity, and low-energy fractures, were most common in the patients with cardiovascular disease or COPD. The frequent use of glucocorticoid therapy was also an important RF in the patients with COPD. CHID considerably increased the risk of fractures in the succeeding 10 years after disease onset. The high risk of fractures, those of the proximal femur in particular, provides a rationale for the need for timely antiosteoporotic therapy in the majority of patients with CNID. The performed investigation demonstrated that the BMD values in the patients with CNID corresponded, on the average, to the osteopenia criteria; the lowest BMD values were recorded in the patients with COPD and associated cardiovascular disease. The severe course of osteopenic syndrome (a BMD decrease that was diagnostically significant for OP concurrent with fractures was observed in one-third of patients with CNID. The patients with cardiovascular disease or COPD showed a high incidence and degree of OP, which allows these diseases to be considered as a RF for decreased BMD. The long-term uncontrolled course of disease, the degree of organ and functional disorders in the patients with CNID, and concomitant use of glucocorticoid therapy contribute to a reduction in BMD. Conclusion. RFs for OP were identified in the majority of patients with CNID. The high risk of fractures due to an obvious BMD decrease in patients with CNID requires timely diagnosis, treatment, and prevention of osteopenia.